ORIENTASI DAN LAYANAN SANTRI ASING DI PESANTREN WALI BAROKAH KEDIRI JAWA TIMUR - M Munawiroh (Badan Litbang dan Diklat Kementerian Agama RI, 2018)
AbstractThis article is written based on the research focusing on foreign students in Pesantren (Islamic Boarding School) Wali Barokah Kediri. This research focused on the orientation (perspective and vision) and service for foreign students in the Pesantren. The research was conducted by using qualitative approach and descriptive method. Data source was obtained through observation, documentation studies, and in-depth interview with the Pesantren leaders, kiai/ustad (religious senior/teacher), and foreign students. The findings in this research were: 1) The foreign students in Pesantren Wali Barokah aimed to achieve Islamic theology or tafaqquh fiddin excellently, accurately, and completely (kaffah), 2) The parents of foreign students were also involved in learning activities in Pesantren Wali Barokah, 3) The foreign students’ vision to study in pesantren is to be guided directly by ustad/ustazah (male and female teachers) who possess articulate Islamic theology (sanad keilmuan Islam) and are faithful to their academic performance. Furthermore, the students can particularly accomplish reading one of the Kutub Sittah holy books and memorize 30 Juz (part/section) of Alquran, and 4) The parents have their expectations that by sending their children to study in pesantren, they will be independent and become high quality human beings. Abstrak Artikel ini merupakan hasil penelitian tentang santri asing di Pesantren Wali Barokah Kediri. Penelitian ini difokuskan pada orientasi (pandangan dan aspirasi) dan layanan asing yang belajar di pesantren tersebut. Penelitian ini menggunaakan pendekatan kualitatif dengan jenis penelitian deskriptif. Sumber data diperoleh melalui pengamatan, studi dokumen dan wawancara mendalam terhadap pimpinan pesantren, kiai/ustad dan santri asing. Hasil temuan penelitian ini antara lain: 1) santri asing belajar di pesantren Wali Barokah bertujuan untuk memperoleh Ilmu agama Islam atau tafaqquh fiddin secara baik, akurat dan lengkap (kaffah), 2) para orang tua santri asing juga sama-sama mengikuti pembelajaran di pesantren Wali Barokah, 3) Aspirasi santri asing belajar di pesantren yaitu memperoleh bimbingan langsung para ustad/ustazah yang memiliki sanad keilmuan yang jelas, serta dipertanggungjawabkan secara akademis. Seliaan itu, secara khusus mereka dapat mengkahatamkan salah satu dari kitab Kutub Sittah dan menghafal Alquran 30 Juz. 4) Sementara itu, harapan orang tua santri belajar di pesantren ini ingin anak-ananya menjadi manusia mandiri dan berakhlak mulia.